Systematic Management of Peer Counseling Programs for Bullying Prevention - Nurmaya, Rosi; Wasliman, Iim (Journal of Innovation and Research in Primary Education, 2025)
Bullying represents a significant challenge in educational settings, affecting students' psychological, social, and academic development. While traditional counseling approaches face limitations due to inadequate counselor-to-student ratios and adolescents' preference for peer communication, peer counseling programs have emerged as promising alternatives for bullying prevention. This qualitative case study examined peer counseling program management at two public high schools in Bandung (SMAN 13 and SMAN 18 Bandung). Data were collected through in-depth interviews with school principals and guidance counselors, participatory observation of program implementation, and documentation review. Thematic analysis was employed to identify patterns across four management domains: planning, organizing, implementation, and supervision. The study revealed a systematic four-phase implementation approach. Planning involved comprehensive needs assessment and objective formulation aligned with school culture. Organization established a three-tier structure comprising guidance counselors as coordinators, teachers as facilitators, and trained students as peer counselors. Implementation featured informal counseling sessions and structured two-component training (basic counseling skills and bullying-specific education). Supervision utilized direct reporting mechanisms and field monitoring, though standardized evaluation criteria were absent. Both schools successfully created safer environments through peer-mediated interventions that leveraged adolescents' natural communication preferences. Findings demonstrate that systematic peer counseling program management effectively contributes to bullying prevention by empowering students as active agents in creating supportive school cultures. The study provides practical frameworks for program implementation while identifying areas requiring enhanced documentation and standardization. Results support previous research showing peer counseling effectiveness while offering detailed insights into operational mechanisms necessary for program sustainability.